(untitled) (Research, Society and Development, 2020)
Cakes are convenience products, however, phenylketonuric patients find them difficult to consume, since most may contain ingredients with proteins such as eggs, albumin and soy-derivates that contribute to their typical sensory attributes. The substitution of these ingredients can cause loss of technological quality reducing its acceptance. The objective of this work was to analyze the sensory characteristics of three muffin formulations free of sucrose, gluten, lactose and restricted in phenylalanine (Phe), containing yam mucilage (MI) and flaxseed gel (GL). Muffin formulations in MI / GL proportions: 37.09 / 11.45 (MRF1); 10/30 (MRF2) and 30/20 (MRF3) were submitted to acceptance tests through a nine points hedonic scale and purchase intention through a five points scale, both structured. There was no significant difference (p> 0.05) for aroma, appearance and color between the muffins, but samples with more flaxseed (MRF1 and MRF3) received significantly higher scores in the attributes of flavor, texture and overall impression (p≤ 0.05). MRF3 with greater addition of MI and GL represents a new option for patients with phenylketonuria, celiac disease and lactose intolerance on the market.